Study Of The Surface Integrity Of AISI 4140 Steel In Wire Electrical Discharge Machining - Mas Ayu, Hassan; N. S., Mehat; S., Sharif; Rosdi, Daud; Siti Haryani, Tomadi; Mohamed Reza Zalani, Mohamed Suffian (2009)
The Wire Electro Discharge Machining (WEDM) process is a violent thermal process where literally thousands of electrical discharges are produced in a fraction of a second in order to erode a certain volume of metal. The process is most used in situations where intricate complex shapes need to be machined in very hard materials (such as hardened tool steel). However, the process generates surface that have poor properties such as high tensile residual stresses, high surface roughness, presence of micro-cracks and micro-voids. These properties vary with different levels of the main machining parameters. The aim of this paper is to present experimental work that has been done in order to quantify the effect of some of the main WEDM parameters on the surface texture of AISI 4140 steel. 2D surface measurements were taken on all WEDM samples and 2D surface characterization has been carried out in order to calculate the different surface texture parameters. In this work, the surface characteristics caused by WEDM were analyzed by Scanning Electron Microscopy (SEM).